An Analysis of Fintech's Role in Facilitating Foreign Exchange Transactions for MSMEs - Nadhifa Maulidia; Alfia Said; Achmad Budi Susetyo (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2025)
This study aims to analyze the role of financial technology (fintech) in facilitating foreign exchange (forex) transactions for Micro, Small, and Medium Enterprises (MSMEs). With the rapid development of digital technology, fintech has emerged as an innovative solution in the financial sector, offering easier access, lower transaction costs, and faster cross-border financial operations. For MSMEs engaged in export and import activities, the ease of forex transactions is crucial to maintaining operational continuity and enhancing business competitiveness. This research uses a descriptive qualitative method through literature review and secondary data analysis. The findings indicate that fintech plays a significant role in promoting financial inclusion, expanding global market access, and increasing the efficiency of forex transactions for MSMEs, especially those in remote areas. However, challenges such as data security and digital literacy remain as obstacles. Therefore, regulatory support and government-led education initiatives are essential to building a healthy and sustainable fintech ecosystem for MSME development.